Short-term report of early glaucoma surgery with a clear lens extraction and an intraocular lens, OMNI canaloplasty, and a HYDRUS microstent: a case series in younger patients - Laroche, Daniel; Desrosiers, Abelard; Ng, Chester (Frontiers in Ophthalmology, 2024)
Purpose The purpose of this case series is to report the surgical outcomes from the combination of a clear lensectomy, OMNI® canaloplasty, and a HYDRUS® microstent with an adjacent goniotomy. Methods This is a retrospective non-comparative single-center case series of four black patients of African descent with glaucoma who were treated with a clear lensectomy, OMNI canaloplasty, and a HYDRUS microstent with an adjacent goniotomy. The surgeries were performed by an experienced cataract and glaucoma surgeon, Daniel Laroche, MD. The parameters investigated in this study were postoperative intraocular pressure (IOP) and the mean number of preoperative and postoperative medications needed. Results The mean age of the four patients was 44.5 years. All patients had a mean postoperative reduction in IOP of 17 mmHg to 12.7 mmHg. The mean number of preoperative medications was 2.2, while the mean number of postoperative medications was 0.3. Potential complications such as hyphema, IOP spikes, or corneal edema were not seen in this series. All patients achieved a lower IOP and stable vision with less refractive error. Patients also experienced improved visual fields, clearer vision, and more open angles. Conclusion Clear lensectomy and combined microinvasive glaucoma surgery (MIGS) in patients with primary open-angle glaucoma (POAG) and narrow-angle glaucoma (NAG) results in the safe lowering of IOP. The limitations of this study include the small series size and the retrospective potential for bias. Further research with a larger series and a prospective trial with follow-up should be performed.